2023
DOI: 10.1002/dad2.12393
|View full text |Cite
|
Sign up to set email alerts
|

Development of digital voice biomarkers and associations with cognition, cerebrospinal biomarkers, and neural representation in early Alzheimer's disease

Abstract: Introduction Advances in natural language processing (NLP), speech recognition, and machine learning (ML) allow the exploration of linguistic and acoustic changes previously difficult to measure. We developed processes for deriving lexical‐semantic and acoustic measures as Alzheimer's disease (AD) digital voice biomarkers. Methods We collected connected speech, neuropsychological, neuroimaging, and cerebrospinal fluid (CSF) AD biomarker data from 92 cognitively unimpair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 56 publications
3
13
0
Order By: Relevance
“…In fact, machine learning (ML) techniques have been developed utilizing various speech and linguistic biomarkers to identify individuals with MCI ( 26 ), early AD ( 27 , 28 ), dementia ( 29 ), Parkinson’s disease ( 30 ), and frontotemporal disorders ( 31 ). For instance, Hajjar and colleagues ( 27 ) found both acoustic and lexical-semantic biomarkers to be sensitive to cognitive impairment and disease progression in the early stages of AD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, machine learning (ML) techniques have been developed utilizing various speech and linguistic biomarkers to identify individuals with MCI ( 26 ), early AD ( 27 , 28 ), dementia ( 29 ), Parkinson’s disease ( 30 ), and frontotemporal disorders ( 31 ). For instance, Hajjar and colleagues ( 27 ) found both acoustic and lexical-semantic biomarkers to be sensitive to cognitive impairment and disease progression in the early stages of AD.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, machine learning (ML) techniques have been developed utilizing various speech and linguistic biomarkers to identify individuals with MCI ( 26 ), early AD ( 27 , 28 ), dementia ( 29 ), Parkinson’s disease ( 30 ), and frontotemporal disorders ( 31 ). For instance, Hajjar and colleagues ( 27 ) found both acoustic and lexical-semantic biomarkers to be sensitive to cognitive impairment and disease progression in the early stages of AD. Several additional studies have demonstrated efficacy of computer-assisted linguistic processing algorithms in detecting speech differences between normal and impaired individuals in the English language ( 32 , 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our own systematic review on the potential of using interactive AI methods to detect AD biomarkers, we concluded that when compared with traditional neuropsychological assessment methods, speech and language technology were at least equally discriminative between different groups. 14 Interestingly, speech-based markers have been found to detect AD pathology such as amyloid‐β status, 19 but evidence also suggests that people with higher amyloid levels (both asymptomatic and those with mild cognitive impairment) exhibit a greater rate of decline in episodic memory and language, 20 suggesting the causal relation between speech and AD pathology should be explored further. Some of the most promising AD markers in speech may be lexico-semantic, 21 meaning the use of deictic words such as those referring to specific time (eg, now, tomorrow), place (eg, here, at home) or person (eg, I, the person).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, vocal deficits and disordered communication also occur early during disease progression, often develop prior to the onset of classic memory and cognitive dysfunction ( Garrard et al, 2005 ; Hajjar et al, 2023 ), worsen over time, and significantly reduce health and quality of life ( Humbert et al, 2010 ; Mueller et al, 2018a ) with devastating associated economic burden ( Woodward, 2013 ). Although signs/symptoms of communication deficits have been traditionally classified as mid-to late-stage events ( Ross et al, 1990 ), recent studies suggest earlier prodromal involvement of other regions in the central and peripheral nervous systems ( Delaby et al, 2015 ; King et al, 2018 , 2019 ; Morris et al, 2019 ; Trushina, 2019 ; Cheng et al, 2020 ; Leuzy et al, 2022a ), potentially directly impacting laryngeal coordination and communication ( Mueller et al, 2018a ; Mahon and Lachman, 2022 ).…”
Section: Introductionmentioning
confidence: 99%